Hubungan Tingkat Tabungan Domestik Bruto Dengan Pertumbuhan Ekonomi - Wawan Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Every development country faces the similar problems about how to boost economics to reach for the prosperity. Many models have developed to help the government plan their economics. This paper with base on Aklilu A. Zegeye's paper presents the alternative model to build the correlation of rate of gross domestic saving and economic growth with simultaneous equation.